Use of metformin as monotherapy in the management of gestational Diabetes mellitus (Research, Society and Development, 2024)
Gestational diabetes mellitus (GDM) is a disorder characterized by a state of glucose intolerance, detected for the first time during pregnancy, resulting in hyperglycemia of variable levels, which may or may not persist after birth. For most women with GDM, monitoring, nutritional guidance and lifestyle changes are sufficient for treatment. However, some women may require drug treatment. Oral antidiabetics (OAD), such as metformin, are not first-choice drugs for the treatment of GDM, but they can be considered in some situations. This work aims to obtain the therapeutic success rate of monotherapy with metformin in pregnant women with GDM, in addition to analyzing the presence of obesity and advanced maternal age as possible factors associated with the disease and treatment. This is a descriptive research, with a quantitative approach, through analysis of medical records of pregnant women with GDM. The results of this study demonstrated that metformin monotherapy was not effective in more than half of the cases, and highlighted the importance of following the most current recommendations for the treatment of GDM. The vast majority of pregnant women (91.8%) had a gestational BMI that constitutes overweight or obesity, highlighting the presence of excess weight as a determining factor in the development of the disease, and the need for adequate prenatal care.